2014
DOI: 10.1055/s-0034-1376661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Boost with TGF-Beta 1 and Grade of Intervertebral Disc Degeneration on 3D Culture of Human Annulus Fibrosus Cells

Abstract: Background: Three-dimensional (3D) culture in porous biomaterials as well as stimulation with growth factors are known to be supportive for intervertebral disc cell differentiation and tissue formation. Unless sophisticated releasing systems are used, however, effective concentrations of growth factors are maintained only for a very limited amount of time in in vivo applications. Therefore, we investigated, if an initial boost with transforming growth factor-beta 1 (TGF-beta 1) is capable to induce a lasting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although TGF‐β1 has been previously demonstrated to promote cellular proliferation and collagen production of various human cells, including AF cells (Jenner et al , ; Wipff and Hinz, ; Turner et al , ), TGF‐β1 showed a negligible effect on AF differentiation of hASCs when supplemented alone. Hegewald et al () consistently showed no significant benefit of addition of TGF‐β1 in 3D culture of AF cells. In the present study, the aggrecan expression was the highest when TGF‐β1 was used in combination with TGF‐β3, however, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although TGF‐β1 has been previously demonstrated to promote cellular proliferation and collagen production of various human cells, including AF cells (Jenner et al , ; Wipff and Hinz, ; Turner et al , ), TGF‐β1 showed a negligible effect on AF differentiation of hASCs when supplemented alone. Hegewald et al () consistently showed no significant benefit of addition of TGF‐β1 in 3D culture of AF cells. In the present study, the aggrecan expression was the highest when TGF‐β1 was used in combination with TGF‐β3, however, the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%